A case of dysarthria - Pranesha Rao BN (Journal of All India Institute of Speech and Hearing, 1970)
Mr  S., aged 33 years reported to the  clinic  on 7-3-1967 with a complaint of misarticulation from  childhood.   The  case  felt that  the  tonsils  operation that  he underwent at the  age of 5 might  have  caused  the  problem. Mothertongue of the case  is Tamil  and  he  knows  English, Hindi and  Sanskrit.     He  is a  graduate. He  has  six  siblings   and   there   was   no   family   history    of  speech    or   hearing defects    or   any    other    illnesses.       No    significant   prenatal    history     except instrumental delivery.      Other   milestones  of   development   were   reported  to be   normal.    The   case   underwent  tonsils   operation  at   the   age   of   5   and tongue  tie  operation at  the   age  of 7.     Otolaryngological examinations  revealed scarring and contraction of soft palate, scarring and retraction of tonsils, and chronic lymphoid hyperplasia of pharynx with  no  unusual infection of upper  respiratory tract.     Neurological  examinations  revealed   normal  reflexes.    No   abnormalities were  noted   with  regard  to  the  functions  of higher  centers   and    cranial   nerves except  for a slight paresis of orbicularis oris and pharyngeal muscles.  Hemiatrophy of the tongue  on right side was also noticed. It was diagnosed as residual  traumatic birth  injury.     There  was no  hearing  loss and  psychological examinations revealed no specific problems relevent  to the defect